A comparison between emission intensity and emission cap regulations. (February 2020) - Hirose, Kosuke; Matsumura, Toshihiro
Abstract: We revisit command-and-control regulations and compare their efficiency, particularly an emission cap regulation that restricts total emissions and an emission intensity regulation that restricts emissions per unit of output under emission equivalence. We find that in both the most stringent target case, in which the target emissions level is close to zero, and the weakest target case, in which the target emissions level is close to business as usual, the emission intensity regulation yields greater welfare than does the emission cap regulation. However, in the moderate target cases, an emission cap regulation may be better in terms of welfare than an emission cap regulation because the emission intensity regulation causes over-production. Our results suggest that the efficiency of a policy measure depends on the target level of emissions. Highlights: We examine command-and-control regulations in an oligopolistic industry. We compare emission intensity and emission cap regulations, given emissions target. The emission intensity regulation is superior when target is close to zero emission. The emission cap regulation may yield greater welfare when target level is moderate. The efficient policy instrument depends on the emission target level.